WebGIS-Based Diagnosis of Economic Vulnerability: Implementing the Inflation Risk-Burden Matrix via a Spiral Development Framework - Eva Febyliana; Teuku Zaine Abror Attolok; Auliya Rohman Riquelme Al Ubaidah; Kilala Mahadewi (Journal of Computing and Smart Ecosystems, 2025)
This study develops a WebGIS application to diagnose regional economic vulnerability using the Inflation Risk–Burden Matrix supported by a Spiral Development Framework. Monthly inflation data from 150 Indonesian cities for 2021–2024 are transformed into two indicators: long-term inflation burden and annual volatility risk. These indicators classify each city into four vulnerability quadrants. Findings show that more than half of the cities fall into the High-Burden & High-Risk category, indicating strong structural pressures and unstable price dynamics. The WebGIS system visualizes these classifications through thematic layers, spatial interaction tools, and automatic diagnostic pop-ups, allowing users to interpret inflation conditions more easily. The study concludes that integrating analytical metrics with spatial visualization enhances diagnostic accuracy and supports more effective, evidence-based decision-making for regional inflation control.